2018
DOI: 10.1108/imefm-08-2017-0198
|View full text |Cite
|
Sign up to set email alerts
|

The role of training in building awareness about formalin abuse: evidence from Bangladesh

Abstract: Purpose This paper aims to assess the impact of the training program on fish traders in building awareness about formalin abuse in food items. Design/methodology/approach Primary data was collected from the fish traders in Bangladesh by using simple random sampling technique. Binary logistic regression was used to assess the opinions of the fish traders about training in building awareness of formalin abuse. Findings This study showed that the training of the fish traders played a positive role in improvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
5
0
3
Order By: Relevance
“…While there are distinct differences in terms of literacy rates, gender equality and other social indicators, the two countries also share certain common characteristics relevant to our research. Both countries have a substantial number of subsistence entrepreneurs operating in SMs in both urban and rural areas, with increasing incidence of malpractice reported in media in both countries (Munasinghe et al ., 2014; Solaiman and Ali, 2014; Shuchi, 2017; Kabir et al ., 2018). In addition, a significant percentage of the labor force works in the informal sector in each country, and most start their own micro‐ventures as entrepreneurs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While there are distinct differences in terms of literacy rates, gender equality and other social indicators, the two countries also share certain common characteristics relevant to our research. Both countries have a substantial number of subsistence entrepreneurs operating in SMs in both urban and rural areas, with increasing incidence of malpractice reported in media in both countries (Munasinghe et al ., 2014; Solaiman and Ali, 2014; Shuchi, 2017; Kabir et al ., 2018). In addition, a significant percentage of the labor force works in the informal sector in each country, and most start their own micro‐ventures as entrepreneurs.…”
Section: Methodsmentioning
confidence: 99%
“…Subsistence entrepreneurs can be viewed as either solely owned businesses or with a maximum of five employees, and those who operate primarily to service subsistence consumers (Azmat and Samaratunge, 2009; Viswanathan et al ., 2014). In recent times, several reports show that a number of subsistence entrepreneurs in developing countries have engaged in business malpractices which can pose serious threats to the wellbeing of their subsistence consumers as they are more vulnerable than their affluent counterparts (Munasinghe et al ., 2014; Solaiman and Ali, 2014; Shuchi, 2017; Kabir et al ., 2018). Such practices may include overpricing, providing misleading information, and selling underweight, contaminated foodstuffs and other essential commodities adulterated with toxins and pesticides (Azmat and Ha, 2013; Mir, 2013; Solaiman and Ali, 2014; Sobhani, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In his work, Umberson (1992), showed that mortality rates among the married women are less than the unmarried womensince they are moreattentivewith regards to their health conditions. Similarly, secondary sources (Mandelblatt et al, 1999;Kabir et al, 2018) found a relationship between age and receiving health care services among women. They showed that elderly women who are more than 65 and above in age, are less likely to undergohealth care screeningthan younger women.…”
Section: Conceptual Frameworkmentioning
confidence: 97%
“…Kandungan formalin pada ikan segar lebih tinggi dari pada ikan pindang. Mungkin karena konsumen lebih memilih membeli ikan segar dengan mempertahankan penampilan maka para pedagang banyak menggunakan formalin pada ikan segar (Hoque, Jacxsens, De Meulenaer, & Alam, 2016;Kabir et al, 2018). Ikan jarang dihinggapi lalat di pasar, teksturnya lembek dan warnanya sedikit putih tidak sama dengan warna asli ikan tersebut.…”
Section: Hasil Dan Pembahasanunclassified